THE EFFECT OF BOARD GENDER DIVERSITY, FINANCIAL BACKGROUND AND PANDEMIC PERIOD TOWARDS THE FINANCIAL PERFORMANCE OF A COMPANY (EMPIRICAL EVIDENCE FROM MANUFACTURING COMPANY LISTED IN INDONESIAN STOCK EXCHANGE) - Mellinda Chrislo; Elfina Astrella Sambuaga (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
This research seeks to determine how gender diversity impact financial performance, how financial background of board impact the financial performance and how pandemic period impact the financial performance of a company. In this study, the population consisted of manufacturing firms listed on the Indonesian Stock Exchange between 2018 and 2020. Purposive sampling was employed as the sampling technique. The sample had a total of 52 companies and a total of 152 observations. According to the three hypothesis that is proposed is that the presence of female directors have a positive impact on the financial performance of the company. The presence of board member with financial background will have a positive impact towards the financial performance and lastly, pandemic period have a negative impact towards the financial performance of the company.